Phenomenology Studies: College Student Experience in Early Childhood Learning Based on Neuroscience Studies - Faizah, Ulinnuha Nur; Al Baqi, Safuruddin; Fadly, Wirawan (Institut Agama Islam Negeri Ponorogo, 2023)
Neuroscience in learning is a study that studies the brain in terms of anatomy and physiology and its correlation with learning. This study analyzed the ability of research subjects to link learning in early childhood with neuroscience studies. This study uses a qualitative method with a phenomenological approach. The research subjects were PIAUD IAIN Ponorogo students taking Neuroscience courses in the 2022/2023 academic year. The learning methods for early childhood analyzed in this study included drum bands, drama, movements and songs, singing, modern and traditional dance, games, and stories or fairy tales presented in work performances. Data collection was carried out through documentation and interviews. The research data were analyzed using the Miles and Huberman Analysis model, which consisted of three steps: reduction, data presentation, and drawing conclusions. Results Analysis of the research data showed that the research subjects could link learning in early childhood with neuroscience studies and knew the importance of learning in early childhood based on neuroscience studies.